Sustainable Energy Planning and Management with cooking and maritime transport electrification, household energy savings and heating sector integration - Poul Alberg Østergaard; Rasmus Magni Johannsen; Neven Duic (International Journal of Sustainable Energy Planning and Management)
This 43rd volume of the International Journal of Sustainable Energy Planning and Management presents contemporary research within the diverse field of energy planning. The issue starts with analyses of an Indian programme targeting the replacement of fossil fuel-based stoves with induction stoves. Another electrification analysis targets maritime transportation and floating offshore charging stations. Third, analyses are presented regarding the potential impacts of household energy savings in Iran, and whether to optimally use savings for unmet demands in industry or for export – or indeed to lower production correspondingly. Two Hungarian studies focus on a comparison of using heat atlas and using measured data for heat planning and on the feasibility of using individual heat pumps as flexibility provider for the electricity system. Taking a Danish case as a starting point, the role of the heating system in the overall energy system transition is analysed and lastly, a study review the literature on city energy planning approaches.